1977
DOI: 10.1113/jphysiol.1977.sp012074
|View full text |Cite
|
Sign up to set email alerts
|

Atrial receptors in the dog and rabbit

Abstract: SUMMARY1. Action potentials were recorded from slips of the cervical vagi in anaesthetized dogs and rabbits. Single functional units with atrial patterns of discharge (Paintal Type A, B and intermediate) were obtained and then attempts were made to alter (i.e. convert) their patterns of discharge. Finally the points of origin of these action potentials were located.2. Thirty unselected units were investigated in thirty dogs. Twentyseven of these were located in the endocardium of the vein-atrial system and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
(44 reference statements)
1
26
1
Order By: Relevance
“…An atrial receptor may have its endings functionally orientated so as to detect atrial filling ('in parallel' orientation), and it could be located in the atrial wall close to another receptor whose endings are functionally orientated so as to detect atrial contraction ('in series' orientation) (Whitteridge, 1953;Recordati et al 1976). Such orientation of atrial endings would explain the following findings, which are in apparent contradiction to those reported by Kappagoda et al (1976Kappagoda et al ( , 1977. First, in our present and previous studies, few type A atrial receptors have been located on the lateral free wall of the right atrium.…”
Section: Re8ponse8 To Active Stretchcontrasting
confidence: 56%
See 3 more Smart Citations
“…An atrial receptor may have its endings functionally orientated so as to detect atrial filling ('in parallel' orientation), and it could be located in the atrial wall close to another receptor whose endings are functionally orientated so as to detect atrial contraction ('in series' orientation) (Whitteridge, 1953;Recordati et al 1976). Such orientation of atrial endings would explain the following findings, which are in apparent contradiction to those reported by Kappagoda et al (1976Kappagoda et al ( , 1977. First, in our present and previous studies, few type A atrial receptors have been located on the lateral free wall of the right atrium.…”
Section: Re8ponse8 To Active Stretchcontrasting
confidence: 56%
“…Pattern of discharge Kappagoda et al (1976Kappagoda et al ( , 1977, demonstrated that the pattern of spontaneous discharge of an atrial receptor is mainly dependent upon its anatomical location. The present study confirms this observation.…”
Section: Re8ponse8 To Active Stretchmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Paintal, 1953;Kappagoda, Linden & Mary, 1977). On the left side of the heart, these receptors are situated mainly at the pulmonary vein-left atrial junctions (Coleridge, Hemingway, Holmes & Linden, 1957;Kappagoda et al 1977). Receptors with nonmyelinated vagal afferent fibres (e.g.…”
Section: Resultsmentioning
confidence: 99%